Pengaruh Fraud Pentagon terhadap Financial Statement Fraud - Azizah, Izmi Hafsah; Pupung Purnamasari; Mey Maemunah (Bandung Conference Series: Accountancy, 2024)
Abstract. This study aims to determine banking companies that experience financial statement fraud using pentagon fraud theory. Pentagon fraud has five factors that influence the cause of someone committing fraud, namely pressure, opportunity, rationalization, competence and arrogance. In this study, the first factor of pressure is proxied with variables of financial stability, financial target, and external pressure. The second factor of opportunity is proxied with the variable ineffective monitoring. The third factor of rationalization is proxied with the variable change in auditor. The fourth factor of competence is proxied with the variable change of director. Finally, the Arrogance factor is proxied with the frequent number variable of the CEO picture. This study uses the fraud score model to test financial statement fraud. The data source used in this study is secondary data. The sampling technique in this study used the purposive sampling method 30 companies were obtained with an observation period of 4 years. The data analysis used was multiple linear regression analysis processed using SPSS 23 software. The results showed that the variables of fraud pentagon financial stability, ineffective monitoring, and frequent number of CEO picture affect of financial statement fraud. While some variables of fraud pentagon external pressure, change in auditor, and change of director have no influence of financial statement fraud. This research is expected to be used as a reference for future research by adding other variables that are not in this study and can use different research objects. Abstrak. Penelitian ini bertujuan untuk mengetahui perusahaan perbankan yang mengalami terjadinya kecurangan laporan keuangan dengan menggunakan teori fraud pentagon. Fraud pentagon mempunyai lima faktor yang mempengaruhi penyebab seseorang melakukan terjadinya kecurangan yaitu pressure, opportunity, rationalization, competence dan arrogance. Pada penelitian ini faktor pertama pressure diproksikan dengan variabel financial stability, financial target, dan external pressure. Faktor kedua opportunity diproksikan dengan variabel ineffective monitoring. Faktor ketiga rationalization diproksikan dengan variabel change in auditor. Faktor keempat competence diproksikan dengan variabel change of director. Terakhir faktor Arrogance diproksikan dengan variabel frequent number of CEO picture. Penelitian ini menggunakan Fraud score model untuk menguji financial statement fraud. Sumber data yang digunakan dalam penelitian ini data sekunder laporan keuangan tahunan perusahaan. Teknik pengambilan sampel penelitian ini menggunakan metode purposive sampling dengan kriteria sampel pada perusahaan perbankan yang terdaftar di Bursa Efek Indonesia periode 2017-2021. Berdasarkan kriteria diperoleh sampel sebanyak 30 perusahaan selama empat tahun periode laporan keuangan. Teknik analisis data yang digunakan analisis regresi linier berganda yang diuji melalui software SPSS 23. Hasil penelitian ini menunjukkan bahwa variabel financial stability, ineffective monitoring frequent number of CEO Picture berpengaruh terhadap financial statement fraud. Sedangkan pada variabel external pressure, change in auditor, change of director tidak berpengaruh terhadap financial statement fraud.